Systematic review of pre-clinical chronic myeloid leukaemia - Kuan, Jew Win; Anselm, Su Ting; Leong, Chooi Fun; Motomi, Osato; Goro, Sashida (Springer Nature B.V., 2019)
The author would like to correct the error in the publication of the original article. The corrected detail is given below for your reading: The first sentence in the last paragraph on page 481 in ‘‘Discussion’’ section under the subheading “Overall completeness and applicability of evidence” should read as “Clonal haematopoiesis of indeterminate potential (CHIP) was first named in 2015 [27].”